Palliative care and oncological patients - Siniša (Scientific Journal of Medical Science, 2020)
Palliative care is an active and holistic concern for both the person whose illness no longer responds to treatment and the patient's family. Palliative care seeks to alleviate pain and suffering and improve the quality of life of the patient and his or her family. Palliative care not only alleviates physical symptoms but also helps with mental, social and spiritual difficulties. Palliative care supports family members during illness and in mourning after the patient's death. Palliative care celebrates life: it does not accelerate or delay death, considering it as part of a normal life process.